Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.22246/jikm.2018.39.4.645
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Domestic Clinical Studies about Clinical and Subclinical Hypothyroidism Treated with Korean Medical Interventions

Abstract: The aim of this paper was to aid Korean clinical practices for determining clinical and subclinical hypothyroidism and to identify further relevant studies by summarizing the present domestic clinical studies. Methods: The research consisted of a review of articles up to July, 2018 found by searching 'Hypothyroidism' and 'Hashimoto's thyroiditis' as keywords in five domestic electronic databases. Results: Only nine studies satisfied the selection criteria and were analyzed. These included six case reports, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous case series reported that Korean medicine using a combined treatment of herbs and acupuncture improved hypothyroidism. [ 28 , 29 ] Herbal medicines, including Leejoong-tang, Bojungikqi-tang, and Saenggangeonbi-tang, were prescribed under similar diagnoses (“Yin deficiency and Yang hyperactivity).” The treatment period ranged from 40 to 184 days. Although the treatment period could be different based on the severity of symptoms, this study had the shortest period of herbal administration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous case series reported that Korean medicine using a combined treatment of herbs and acupuncture improved hypothyroidism. [ 28 , 29 ] Herbal medicines, including Leejoong-tang, Bojungikqi-tang, and Saenggangeonbi-tang, were prescribed under similar diagnoses (“Yin deficiency and Yang hyperactivity).” The treatment period ranged from 40 to 184 days. Although the treatment period could be different based on the severity of symptoms, this study had the shortest period of herbal administration.…”
Section: Discussionmentioning
confidence: 99%